Linguistic diversity in a rural Northern Cape municipality : a sociolinguistic investigation of Gamagara local municipality - Vollmer, Tracey; Bates, Tracey (Stellenbosch : Stellenbosch University, 2019)
Thesis (MA)--Stellenbosch University, 2019.